(untitled) (International Journal of Food and Nutritional Sciences, 2023)
In gift situation homes with drifting segment is a standard trademark withinside the forefront multistorycreation in city India. Such abilities are generally undesirable in building built in seismicallyvivacious regions. This view features the meaning of expressly recognizing the presence of thedrifting segment withinside the assessment of building